Human population dynamics : cross-disciplinary perspectives - Macbeth, Helen M.; Collinson, Paul, 1969- (Biosocial Society symposium series, 2002)
Human Population Dynamics is an introductory text demonstrating how changes in human population structure can be addressed from multi-disciplinary perspectives. As such, it contains contributions from specialists in demography, social and biological anthropology, genetics, biology, sociology, ecology and human geography. This text is aimed at academic researchers, graduates and undergraduates.